Pengembangan Sistem Manajemen Surat (SMART) sebagai Solusi Permasalahan Arsip Surat di Kantor Bea Cukai Malang - Akbar, Muhammad Iqbal; Ayudhitama, Annisa Putri; Smaragdina, Azhar Ahmad; Soraya, Dila Umnia (Jurnal Teknologi Informasi dan Pendidikan, 2024)
The study aims to create a digital mail management system, known as SMART, to address the inefficiencies of the current manual letter archiving system at the Malang Customs and Excise Supervision and Service Office. The existing system, which relies on Microsoft Excel, is time-consuming and prone to errors. This leads to difficulties in searching for specific letter scans and the potential loss of hard-file archives. The SMART system, designed using the Waterfall Method and the CodeIgniter framework, is a web-based information system that allows the management of incoming, outgoing, and internal letters in a digital format. The system includes features such as inserting, updating, and deleting letters, as well as uploading scanned letter files. According to the System Usability Scale (SUS) test results, the SMART application is highly usable, with an average score of 93.50, which exceeds the benchmark of 68. The implementation of SMART is expected to significantly improve the efficiency of the administration section's document archiving process, enhancing the accessibility and management of letter archives at the Malang Customs and Excise Supervision and Service Office.